Teori Kepemimpinan Islam: Konsep Imamah Al-Ahkam Al-Sultaniyyah dan Asabiyah dalam Al-Muqaddimah - Muhammad Rifqi Shiddiq; Jufri Yahya (Ma'had Aly Raudhatul Ma'arif, 2026)
This study is motivated by various contemporary leadership issues, including declining public trust, weak accountability, and increasing social conflicts. In this context, the leadership theories of Al-Mawardi and Ibn Khaldun are important to examine as theoretical foundations of Islamic leadership. The problem addressed in this study is how leadership is conceptualized by al-Mawardi and Ibn Khaldun and its relevance to modern society. The research questions focus on identifying the characteristics of ideal leadership according to both scholars and examining their application in contemporary social life. This study employs a qualitative method with a library research approach, analyzing primary sources such as al-Ahkam al-Sultaniyyah and al-Muqaddimah, as well as other relevant supporting literature. The findings reveal that, according to al-Mawardi, leadership (imamah) is normative in nature, emphasizing justice, trustworthiness, and legitimacy. In contrast, Ibn Khaldun highlights sociological aspects such as social solidarity (asabiyyah), stability, and the dynamics of society. This research seeks to integrate al-Mawardi’s normative approach with Ibn Khaldun’s empirical perspective in order to formulate a more comprehensive model of Islamic leadership. The study concludes that ideal leadership is a combination of normative values and social realities, making it highly relevant for application in modern society